PENGARUH PEMBIASAAN BERJABAT TANGAN TERHADAP KEDISDIPLINAN ANAK MADRASAH IBTIDAIYAH - Siti Fathonah; Syarifan Nurjan; Anip Dwi Saputro (TARBAWI:Journal on Islamic Education, 2020)
This study aims to find out the influence of the habit of shaking hands on the discipline of MI children. The object of research is a student of class III, IV V of which 140 children. Meanwhile, for the sampling technique using random sampling. In measuring the research variable, research first test the instrument, the validity test, and the reliability test. Meanwhile, in measuring the effect of both variables using the formula of correlation and simple linear regression using the SPSS 21. Based on the test result the coefficient of determination (R square) obtained a correlation value of 0,390, meanwhile the R square (R) value of 0,390. This means that the percentage of contribution to the effect of shaking hands on increasing children’s discipline has a quite good and significant influence